113. Accuracy of the NHSN Central Line-Associated Bloodstream Infection (CLABSI) Definition. (26th November 2018) - Hammadi, Ahmed Al; Ostrosky-Zeichner, Luis; Boston, Kelley; McInnis-Cole, Tawanna; Butler, John
Abstract: Background: CLABSIs are serious infections that cause prolonged hospital length of stay, increased cost, and mortality. Acute care hospitals must report CLABSIs to NHSN to participate in CMS programs. NHSN definitions must be met to attribute a secondary BSI (SBSI), or bacteremia is defaulted to CLABSI if a central line is present. The lack of CDC/NHSN definitions for certain secondary sites of infections or problems in the definitions may lead to over-labeling CLABSIs. We reviewed the accuracy of NHSN definitions in a large healthcare system. Methods: We retrospectively reviewed medical records of 279 patients with positive blood cultures on or after hospital day 3 and a central line from 15 hospitals belonging to a large healthcare system from January 1 to November 27, 2017. A team of centralized infection preventionists (IPs) adjudicated each case as a CLABSI or as SBSI through routine surveillance following NHSN methodology. A clinical review was performed by a PGY6 infectious diseases fellow. Descriptive statistics are presented. Results: A total of 279 bacteremia cases were analyzed. Of those 279 patients, 237 (85%) were ≥18 years old, 162 (58%) were males, 92 (33%) were white, 62 (22.2%) were black, 5 (1.8%) were Asian, and 12 (4.3%) were "other." Ninety-seven (34.8%) were from the reference hospital. IPs classified 171 CLABSIs and 108 as SBSI. Of the 171 CLABSIs classified by IPs, in 62 patients (36.3%), a primary site infection clinically explaining the BSI, but which did not meet the NHSN infection criteria, could be attributed as follows during the clinical review: 30 pneumonia, 6 urinary tract infections, 4 surgical site infections, 2 vascular infections, 2 mucosal barrier injury associated blood stream infections, 7 gastrointestinal infections, 1 decubitus ulcer infection, 4 skin and soft-tissue infections, 2 left ventricular-assisted device infections, 2 endocarditis, and 2 infected thrombi. Misclassification most often occurred due to missing elements of the definitions or infections not defined by NHSN. Conclusion: Current NHSN definitions may overestimate CLABSIs by nearly 30%. As hospitals continue to work in CLABSI reduction, accurate and precise definitions/methodology will be key in focusing efforts and attention of the engaged parties and avoiding penalties. Disclosures: L. Ostrosky-Zeichner, Cidara Therapeutics: Grant Investigator, Research grant.